Rethinking legibility in the era of digital mobile maps: an empirical study. Issue 3 (4th May 2021) - Ahmadpoor, Negar; Smith, Alastair D.; Heath, Tim
ABSTRACT: This paper examines the role of environmental legibility in an era where digital mobile maps guide many everyday journeys. This paper presents data from a real-world navigational experiment, where participants followed urban routes either by using digital maps, or information in the world around them. They then completed an in-field task that probed recognition for environmental features along the routes. As predicted, participants in the digital map group demonstrated poorer memory for elements that underlie legibility, across landmarks, paths, and nodes. However, recognition in this group was moderated by individual characteristics of these elements, suggesting a role for legibility in memory. The paper discusses the implications of these results for the design of urban environments that can militate against varied navigational experiences.